2016
DOI: 10.1080/03091902.2016.1226438
|View full text |Cite
|
Sign up to set email alerts
|

A novel puborectalis muscle artificial anal sphincter system with the module of sensory perception

Abstract: This article presents a novel puborectalis muscle artificial anal sphincter system (PM-AASS) with the module of sensory perception for treating severe faecal incontinence (FI). Due to the implantable feature of PM-AASS, this system applied low-power design and the total energy consumption could drop to 48.8 Ah/d. To reduce the injury of intestine and the pressure exerted on intestine, the actuator, including the structure of tings and the robot mechanism, of PM-AASS was presented and the middle ring was optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…However, in prior in vivo experiments, it was shown that hyperplasia wrapped the nylon-12 rotatable arm and caused mechanical failure, approximately 2 months after implantation. [5][6][7][8][9] Thus, although the PAAS improves many defects which occurred in previous AAS systems, it is limited by the influence of hyperplasia. Accordingly, there are still obstacles in the application of the system in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…However, in prior in vivo experiments, it was shown that hyperplasia wrapped the nylon-12 rotatable arm and caused mechanical failure, approximately 2 months after implantation. [5][6][7][8][9] Thus, although the PAAS improves many defects which occurred in previous AAS systems, it is limited by the influence of hyperplasia. Accordingly, there are still obstacles in the application of the system in clinical practice.…”
Section: Introductionmentioning
confidence: 99%